2015
DOI: 10.1007/s10815-015-0459-5
|View full text |Cite
|
Sign up to set email alerts
|

Live birth rates using conventional in vitro fertilization compared to intracytoplasmic sperm injection in Bologna poor responders with a single oocyte retrieved

Abstract: Conventional IVF and ICSI are associated with similar reproductive outcomes in poor responder patients with a single oocyte retrieved. Therefore, the choice of fertilization method should be based primarily on semen quality, in combination with the patient's previous history. A randomized controlled trial should be performed to confirm this study's findings that conventional IVF and ICSI have similar reproductive outcomes in poor responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 50 publications
(52 reference statements)
1
23
0
1
Order By: Relevance
“…Despite the variations in definitions, all studies exemplified the limitation of what was stated earlier: a lack of proof that ICSI improved LBR or FR. A retrospective study from 1991-2016 using the national Human Fertilisation and Embryology Authority (HEFA) database singled out over 60,000 cycles meeting criteria for POR with autologous oocytes [25]. The LBR per cycle was equal between the two groups (IVF: 12.2% and ICSI: 12.4%), as was TFF [25].…”
Section: Poor Ovarian Reservementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the variations in definitions, all studies exemplified the limitation of what was stated earlier: a lack of proof that ICSI improved LBR or FR. A retrospective study from 1991-2016 using the national Human Fertilisation and Embryology Authority (HEFA) database singled out over 60,000 cycles meeting criteria for POR with autologous oocytes [25]. The LBR per cycle was equal between the two groups (IVF: 12.2% and ICSI: 12.4%), as was TFF [25].…”
Section: Poor Ovarian Reservementioning
confidence: 99%
“…A retrospective study from 1991-2016 using the national Human Fertilisation and Embryology Authority (HEFA) database singled out over 60,000 cycles meeting criteria for POR with autologous oocytes [25]. The LBR per cycle was equal between the two groups (IVF: 12.2% and ICSI: 12.4%), as was TFF [25]. A 2015 study also specifically utilized the Bologna criteria to determine if ICSI is beneficial in those with POR and NMF.…”
Section: Poor Ovarian Reservementioning
confidence: 99%
“…There was a trend of lower pregnancy rate per cycle after ICSI as compared to IVF, with the implantation rate even being statistically higher after IVF. Since then, there have been no new large RCTs on this topic, or they have just focused on couples with specific diagnostic categories (Fan et al , 2012; Komsky-Elbaz et al , 2013; Sfontouris et al , 2015). A recent large, observational study based on national data from the USA has demonstrated that in non-male factor cycles, ICSI use was associated with lower rates of implantation compared to conventional IVF (23.0% versus 25.2%, respectively; adjusted RR, 0.93; 95% CI, 0.91–0.95) and live birth (36.5% versus 39.2%, respectively; adjusted RR, 0.95; 95% CI, 0.93–0.97) (Boulet et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…6 While ICSI has resulted in high success rates in couples treated for severe male factor infertility, studies have indicated that ICSI offers no advantage over conventional IVF in nonmale factor infertility couples when it comes to live birth rates. [7][8][9][10][11] Moreover, the American Society for Reproductive Medicine recently published a committee opinion stating that 'in cases without male factor infertility or a history of prior fertilisation failure, the routine use of ICSI for all oocytes is not supported by the available evidence'. 12 In the US study from 2018, the large increase in use of ICSI was correlated with a 7.6% (p=0.001) increase in live birth rates per cycle in women younger than 35 years.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%